Location decisions of sport manufacturing businesses in tourism destinations - analysing factors of attractiveness - Elisabeth Happ (Bern Open Publishing, 2020)
Business location criteria and destination attractiveness have been widely studied a) in international business research and b) in tourism research. By contrast, studies about the attractiveness of tourism destinations as possible business locations for sport manufacturing companies have barely been examined. In order to contribute to closing this research gap, the present quantitative study provides insights based on destination attractiveness by analysing sport, tourism, and specific economic attractiveness variables (conducted in the German-speaking Alps; N=119 sport manufacturing companies; based on the Competitiveness Theory of Porter). These variables are represented by nine factors measured by 36 items considered pertinent for alpine tourism destinations. This quantitative study offers an approach to the analysis of attractiveness factors specifically in the context of location decisions by sport manufacturing companies. Results show that 1) sport-specific factors like "Sport Events" and "Sport & Infrastructure" influence a sport manufacturing business's choice of location, 2) cross-cultural differences were identified relating to the importance of specific factors. Furthermore, implications for governments and destination managers were derived, allowing conclusions about competitive advantages. Based on the results, benchmarking destinations and benchmarking initiatives can be identified for the future.